Similarities And Differences Of English And Malay Feline Proverbs: A Conceptual Metaphor Approach - Adilah, Siti Mukhlisa Mohamad Khairul (2022)
This study aims at analysing the disparity of the feline representations with the search for their similarities and differences, as well as exploring the cross-cultural differences between English and Malay feline proverbs, with 24 and 42 proverbs respectively. It is an attempt to scrutinize the underlying meanings associated with the conceptualisation of feline animals and the influence of various cultural backgrounds behind the inauguration of feline representations in the proverbs. A two-phase analysis comprises of the Conceptual Metaphor Theory (CMT) framework by Lakoff and Johnson (1980) and the Great Chain of Metaphor Theory (GCM) framework by Lakoff and Turner (1989) is utilised in the process to achieve the purposes of this study. The first framework entails the identification of conceptual domains and representations that the proverbs carry along with the commonalities and variations available in both languages, and the latter framework focuses on the four components, namely the Naïve Theory of the Nature in Things, the Great Chain of Being, the Generic is Specific Metaphor, and the Maxim of Quantity; to explore the differences based on the crosscultural factors in the proverbs. The results of the study revealed that there are fewer conceptual metaphors available in the English feline proverbs compared to the Malay feline proverbs, and the metaphorical conceptualization of the feline animals in the proverbs is not restricted to the domain of people only, but also incorporated into other domains, including the aspects of affairs, rank, weather, purpose, and life.